Formulation of Liquid Compound Fertilizer Enriched with Nutritional Elements for Shallot Plants on Inceptisol Reuleut Soil - Fahira, Fahira; Akbar, Halim; Ismadi, Ismadi; Handayani, Selvy; Nazirah, Laila; Muliana, Muliana (Malikussaleh University, Aceh, Indonesia, 2025)
Shallots (Allium ascalonicum L.) are one of the leading vegetable commodities in Indonesia that have many benefits, such as a flavouring for cooking spices, raw materials for the food industry, and traditional medicinal ingredients. Inceptisol is a soil with a low content of essential nutrients. However, it can still be pursued with the proper technological handling, one of which is the application of Liquid Compound Fertilizer (PMC). This study aims to determine the effectiveness of the liquid compound fertilizer (PMC) formula applied to Inceptisol soil on the growth and yield of shallot plants. This research was conducted at the Experimental Garden, Faculty of Agriculture, Malikussaleh University, from November to December 2023. This study used a single-factor Complete Randomized Design (RAL) with five replicates. PMC treatment consists of 5 levels, namely (K0) Control, (K1) PMC 25%, (K2) PMC 50%, (K3) PMC 75%, and (K4) PMC 100%. The results showed that applying PMC could increase the growth of shallots in the number of cloves and wet and dry crop weight with a PMC concentration of 50%. And PMC treatment of 75% can increase plant height. PMC treatment is 100% able to increase the number of leaves/plants. The application of PMC can affect the chemical properties of the soil, namely increasing the soil's pH value (H2O) by 0.84%, the soil organic by 1.5%, the total N by 2.73%, and the available P by 5.62%.